IMPLEMENTATION OF DIVISION SIGNS IN SOME NUMBER SYSTEMS (American Journal of Pedagogical and Educational Research, 2024)
This article is devoted to signs of division of numbers in some number systems: 3, 4, 5, 6 number systems are divisible by 2, 4, 5, 6 number systems are divided by 3, hexadecimal number system is divided by four.